Relevansi Kinerja Keuangan Bank Syariah Indonesia terhadap Pertumbuhan Keuangan Syariah di Indonesia - Satar, Muhammad; Nur Jamilah Ambo; Suryadi Kadir (Al Rikaz: Jurnal Ekonomi Syariah, 2024)
This study aims to determine the importance of the financial performance of Bank Syariah Indonesia (BSI) in growing the potential of Islamic finance in Indonesia, considering that the growth of Islamic finance in Indonesia was previously still trying to develop compared to Islamic finance in other Islamic countries such as Malaysia and Saudi Arabia. Through this research, it can also be used as a reference to increase the spirit of using Islamic financial products. The research method for assessing the growth of Islamic finance is the library method, namely collecting library data (books, journals, documents), reading and managing research materials, also taking most of the financial performance data from the Indonesian Sharia Bank (BSI)Annual Report. The results of the study show that the average financial performance of Bank Syariah Indonesia experienced extraordinary growth at a very young age compared to the previous year before the merger of three Islamic banks (BRI Syariah, BNI Syariah and Bank Syariah Mandiri). This indicates that Islamic finance is growing so rapidly in Indonesia and is able to realize Indonesia's ideals of becoming the center of Islamic finance in the world